Análise das estratégias, condições e obstáculos para implantação de técnicas mais sustentáveis para tratamento local de efluentes sanitários residenciais. Caso: assentamento rural Sepé-Tiaraju, Serra Azul-SP - Martinetti, Thaís Helena (Universidade Federal de São Carlos, 2009)
The lack of sanitation systems is one of the main causes of insalubrity and environmental degradation. The term sustainability has provoked a debate in the literature, derived, mainly with the environmental concern and the use of the non-endless natural resources. Besides environmental and ecological issues, the concept incorporates the economical, social, cultural and political dimensions. The last one emphasizes the people participation on making decisions, management and general control of the production process, through the comprehension of the reality and the analysis of different alternatives. The use of participatory processes for taking decision to the choice of more sustainable domestic wastewater system, besides easing the knowledge transfer, permit access to the nonconventional techniques. General purpose was to analyze the strategies, conditions and obstacles for the implantation of more sustainable domestic wastewater systems, containing as experimental object the Rural Settlement Sepé-Tiaraju, located in Serra Azul-SP (Brasil), considering the participatory process for families taking decisions. General strategy used was the participatory action research, which the researcher and the families interact with each other in a cooperative and participatory way. General steps of the action were: 1- participatory process for domestic wastewater systems choice; 2- executive project and the budget system; 3- execution plan of the pilot system; 4- family organization for the execution of the pilot system; 5- the execution of the pilot system; 6- the system maintenance and utilization instructions. For each verified hypothesis, it was elaborated a spreadsheet in where it was explained: the type of information (variable), the evidence sources, the proceedings for the data collection and analysis. It was used as evidence sources the reports, the spreadsheets, the audiovisual images from the discussion meetings with the families and the execution of the domestic pilot wastewater system. Products were: 1- characterization of the domestic wastewater system choice by participatory process for the case of rural settlement Sepé- Tiaraju; 2- characterization of the domestic pilot wastewater system execution by participatory process; 3- sustainability and the participatory action research analysis for the more sustainable domestic wastewater system implantation. Results indicate that the use of participatory process enables the information access, the choice of non-conventional techniques and more sustainable, although it takes more time of the evolved actors (researcher and families) and the adequacy of the activities to the social reality and the capacity of comprehension of the participants. Challenges are related to the actors governance, conflicts and financial resources governance, besides the match of disposable time for the research and the action in the social reality.
Keywords: Áreas residenciais; Tratamento de esgoto; Sustentabilidade; Participação social; Assentamento rural; Saneamento ambiental; Tratamento de efluentes sanitários; Environmental sanitation; Domestic wastewater treatment; Sustainability; Participatory process; Rural settlement; ENGENHARIAS